(untitled) (Global Journal of Medical Research, 2020)
The work shows the role of the autonomic Nervous system in functioning of long-term memory, the identity of functioning of the mechanisms of long-term memory in the evolutionary adaptation of a man and dependence on psychoactive substances. It is shown that the dependences of the body on psychoactive substances are the states of progredient adaptation, that the states of dependence of the organism on psychoactive substances and on psychogenic psychoactive factors are the states of the same type. Classification of psychoactive factors is given. It is proposed to create a new branch of medicine combining study of the body’s dependence both on chemical and psychogenic psychoactive factors. Onomastic definitions to be used in this new branch of medicine are presented Keywords: hypermnesia, engrams of euphoria or any other psychotropic effect, desirable from the point of view of the consumer.